Дрожь: [роман] / Элли Рейнолдс ; [перевод с английского М. Жуковой] - Рейнолдс Элли (Inspiria, 2022)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 57879 / Цена: 427.25 / Сис.шифр: 84(4/8) / Авт.знак: Р 35 / ГРНТИ: 17.82 / ББК: 84(4Вел)-44